Humanity on Mars: Reflections on an Interplanetary Future, between a Technological Utopia and Ethical and Political Dilemmas - Javier Aranda Prieto (RHS Revista Humanismo y Sociedad)
This article reflects on the potential social, political, and cultural scenarios that may emerge from the establishment of human societies on Mars. By analyzing factors such as time, space, terraforming, genetic engineering, and artificial intelligence the authors argue that Martian colonization should not be viewed merely as a technological milestone, but rather as a profound challenge to the construction of human institutions and values in non-Terrestrial contexts. The text explores identity and geopolitical tensions that could arise between Earth and Mars and underscores the urgent need to develop interplanetary institutions capable of guaranteeing justice, cooperation, and sustainability. The article contends that human survival beyond Earth will only be possible if accompanied by an ethical and humanistic commitment that avoids repeating the historical mistakes made on our home planet.